2022
DOI: 10.1186/s13063-022-06053-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving adherence to acute low back pain guideline recommendations with chiropractors and physiotherapists: the ALIGN cluster randomised controlled trial

Abstract: Background Acute low back pain is a common condition, has high burden, and there are evidence-to-practice gaps in the chiropractic and physiotherapy setting for imaging and giving advice to stay active. The aim of this cluster randomised trial was to estimate the effects of a theory- and evidence-based implementation intervention to increase chiropractors’ and physiotherapists’ adherence to a guideline for acute low back pain compared with the comparator (passive dissemination of the guideline)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…We found a 3.4% utilization rate for referral for imaging, which is lower than the previously reported 12% utilization at the same teaching institution [8] and the reported range between 8 and 33% for lumbar imaging utilization in other chiropractic teaching clinics [8,16,26]. Our utilization rate is also considerably lower than the 40% utilization rate reported in Canadian and American field chiropractors referring patients for radiographs with non-specific LBP [17], but similar to the 3% reported by French et al in 2022 in a clinical trial aimed to reduce inappropriate imaging in primary care [19]. Possible explanations for the lower rate at our chiropractic institution include organizational emphasis and implementation of guidelines [6,8,19,27,28], teaching an evidence-based curriculum, discouraging routine and repeat radiographic examinations in the absence of red flags [6,16,28,29], and potential under-use [4].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We found a 3.4% utilization rate for referral for imaging, which is lower than the previously reported 12% utilization at the same teaching institution [8] and the reported range between 8 and 33% for lumbar imaging utilization in other chiropractic teaching clinics [8,16,26]. Our utilization rate is also considerably lower than the 40% utilization rate reported in Canadian and American field chiropractors referring patients for radiographs with non-specific LBP [17], but similar to the 3% reported by French et al in 2022 in a clinical trial aimed to reduce inappropriate imaging in primary care [19]. Possible explanations for the lower rate at our chiropractic institution include organizational emphasis and implementation of guidelines [6,8,19,27,28], teaching an evidence-based curriculum, discouraging routine and repeat radiographic examinations in the absence of red flags [6,16,28,29], and potential under-use [4].…”
Section: Discussionsupporting
confidence: 81%
“…All patients who were imaged had at least one red flag, although only 4% of patients with any red flags were referred for imaging. This later proportion may suggest underutilization; however, current literature suggests red flags should not be considered in isolation but used in consideration of the entire clinical context of the patient [6,8,19,23]. Instead, application of criteria considering sensitivity and specificity of red flags would be more appropriate [4], which was considered by Bussieres et al when they grouped specific red flags by condition, as typically encountered in a clinical context [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66,67 In the ALIGN cluster randomized trial, French et al compared the effectiveness of a tailored, multi-faceted intervention based on guideline recommendations aiming at reducing inappropriate imaging referral and improve outcomes to passive dissemination of the guideline in people seeking care for acute back pain from physiotherapists and chiropractors in Victoria, Australia. 68 They found that clinicians in the intervention group were more likely to provide advice about staying active, but there were no important differences in X-ray referral and no difference in patient outcomes. Finally, Taylor et al compared the effectiveness of a participative group intervention that introduced cognitive behavioral approaches designed to promote self-management to usual care and relaxation music.…”
Section: Ex a M Ple S Of I N T Erv En T Ions De Sign Ed To Fac I L I ...mentioning
confidence: 96%
“…Outcomes from people receiving GLA:D are systematically followed in clinical registries and data are made public 66,67 . In the ALIGN cluster randomized trial, French et al compared the effectiveness of a tailored, multi‐faceted intervention based on guideline recommendations aiming at reducing inappropriate imaging referral and improve outcomes to passive dissemination of the guideline in people seeking care for acute back pain from physiotherapists and chiropractors in Victoria, Australia 68 . They found that clinicians in the intervention group were more likely to provide advice about staying active, but there were no important differences in X‐ray referral and no difference in patient outcomes.…”
Section: Examples Of Interventions Designed To Facilitate High‐value ...mentioning
confidence: 99%